Perencanaan Ulang TPS Limbah B3 Rumah Sakit di Surabaya - Muhammad Farhan Khatami; Mohamad Mirwan (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
A Class B hospital in Surabaya reported that it had established a temporary storage facility for hazardous waste, but that it had yet to meet existing legal standards. The purpose of this preparation is to improve the temporary storage of hazardous waste according to the provisions of the law. Regulation No. 6 of the Minister of the Environment of 2021 and Decision No. 1 of 1995 of the Chairman of the Board of Environmental Impact Management (Bapedal). The study began with on-site observations to assess the current state of the temporary storage facility for hazardous waste, collect data on variations in the type and nature of hazardous waste, including measuring the mass and capacity of the waste generated. A plan for the design of a new temporary storage facility for hazardous waste was then developed. The results of the study showed that the characteristics of the waste generated by the hospital included infectious, flammable liquids, flammable solids, corrosive and toxic substances. According to the study results, the hazardous waste temporary storage area is 63.95 m2 and the requirements include separators for different waste characteristics, two pallet systems, packaging requirements of four 200-litre iron drums, two 100-litre plastic drums, eleven 600-litre silos, eight 150-litre and 50-litre plastic containers, a lighting requirement of ten 19-watt fluorescent lamps, a ventilation area of 6.4 m2, a holding tank capacity of 0.35 m3 for the hazardous waste temporary storage area, two fire extinguishers of 5 kg each and an emergency door.%MCEPASTEBIN%